ANALISA DAN EVALUASI KURIKULUM PROGRAM S1 - Iffah Budiningsih; Khasanah Khasanah (Akademika, 2015)
The purpose of analysis and evaluation of curriculum S1 UIA is to look at thecurriculum S1 currently used are still relevant to needs of student of UIA as the curriculum inorder to improve the quality of kearning proces in the UIA. Teh number of samples usedevaluation as many as 127 students of teh seventh of teh academic year 2015/2016.Curriculum evaluation instrument involves seven indicators that were previously tasted thevalidity and reliability of the instrument. The validity of test results using r product momentis valid all with values between 0,608 – 0,691. The results of reliability test using AlphaCronbach shos coeffcient was 0,8084. Thus the curriculum instruments used as valid andreliabel measurement tools.The finding are as follow : curriculum S1 UIA program that is currently used as thestructure of curriculum, the composition of the subject and the number of credit (SKS) betwencore curriculum and institutional curriculum is still relevant use, both in term of standard ofHigher Education as well as the needs of students.